2010
DOI: 10.1017/s0025315410001785
|View full text |Cite
|
Sign up to set email alerts
|

On the diet and reproduction of the oilfishRuvettus pretiosus(Perciformes: Gempylidae) in the eastern Mediterranean

Abstract: The oilfish,Ruvettus pretiosus, is an incidental by-catch of the drifting surface longlines targeting swordfish and Thunnidae in the Mediterranean and elsewhere. Despite its global distribution and frequent occurrence in the catch of many fishing gears, little is known about its biology. In this study we examined the dietary preferences and reproductive biology of this species from specimens caught in the eastern Mediterranean. The most numerous and frequently occurring prey items were benthopelagic fish, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…No information on the spawning season exists for escolar and snake mackerel. GSIs in the present study compared with the season were consistent with spawning in mid‐ to late summer for oilfish (Vasilakopolous et al., ) and longnose lancetfish spawning year‐round (Nakamura and Parin, ). GSI data in the present study suggested that snake mackerel also spawn year‐round.…”
Section: Resultssupporting
confidence: 80%
“…No information on the spawning season exists for escolar and snake mackerel. GSIs in the present study compared with the season were consistent with spawning in mid‐ to late summer for oilfish (Vasilakopolous et al., ) and longnose lancetfish spawning year‐round (Nakamura and Parin, ). GSI data in the present study suggested that snake mackerel also spawn year‐round.…”
Section: Resultssupporting
confidence: 80%
“…The oilfish Ruvettus pretiosus (Cocco, 1829) is a cosmopolitan benthopelagic fish (Froese & Pauly, 2014). In the Mediterranean, it is an incidental low-value bycatch of surface and demersal longlines (Vasilakopoulos et al, 2011). Previous studies of the species' biology have focused on its diet, reproduction and morphometrics (e.g.…”
Section: Otolith Dimensions-fish Length Relationships Of the Phaeton mentioning
confidence: 99%
“…Previous studies of the species' biology have focused on its diet, reproduction and morphometrics (e.g. Vasilakopoulos et al, 2011). No information on species' growth is available in the relevant literature, or in FishBase (Froese & Pauly, 2014).…”
Section: Otolith Dimensions-fish Length Relationships Of the Phaeton mentioning
confidence: 99%
“…For example, the oilfish Ruvettus pretiosus Cocco (1833) and the short-finned pilot whale Globicephala macrorhynchus Gray (1846) occur together and use the same resources: they both prey on squid and fish (Overholtz & Waring, 1991;Vasilakopoulos, Pavlidis & Tserpes, 2011). The oilfish is mesopelagic; it ranges between 100 and 800m deep, but it is more common not deeper than 400m (Nakamura & Parin, 1993).…”
mentioning
confidence: 99%